Science through Sepedi: Is Terminologisation a Worthwhile Venture? - Carstens, Adelia (Lexikos, 1999)
The terminologisation of the African languages has been hotly debated for more than a decade, yet little progress has been made in devising strategies to guide this process. The following are among the indicators that the time is ripe to realise the ideal of terminologisation: the lack of success thus far achieved in facilitating scientific knowledge through non-mother-tongue education; the existence of a noteworthy stock of technical terms in the African languages; and the positive attitudes of educators towards the use of the mother tongue, especially in rural areas. These indicators are backed up by statistics on pass rates for Physical Science in the Northern Province; the results of an attitude/opinion survey among teachers of Science in this region; lexical data obtained from an empirical survey as well as from an independent source. The results of the research seem to validate terminologisation of Sepedi from an educational point of view. It is, however, realised that the attitudes and perceptions of other stakeholders such as pupils and parents need to be taken into account when recommendations are made with regard to sensitive issues such as terminologisation and the language of scientific communication.